Carbon Footprint Analysis of Processing Tomato Cultivation in Greece - Ioannis ROUSSIS; Ioanna KAKABOUKI; Panteleimon STAVROPOULOS; Antonios MAVROEIDIS; Marilena PAPATHEODOROU; Dimitrios VATOUGIOS; Aikaterini TSELA; Dimitrios BILALIS (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Horticulture, 2023)
Agriculture contributes to global warming through the emissions of greenhouse gasses (GHGs). As one of the most important horticultural crops, tomato (Lycopersicon esculentum Mill.) is of great economic importance.  Approximately 80% of the tomatoes grown around the world are processed into sauces, juices, ketchup, canned tomatoes, and soups. The goal of the present study was to assess the carbon footprint of commercially grown processing tomatoes in Greece. The emissions were calculated by using the Cool Farm Tool software. For data collection, a questionnaire was distributed to processing tomato producers. The questionnaires were completed by 40 producers from the main processing tomato-growing regions of Greece. The estimated total carbon footprint value of tomato cultivation for a mean area of 7.16 ha (producing 94.8 tn of tomatoes per ha) was 1,369,700 kg CO2-eq. Specifically, the estimated carbon footprint values per hectare and kg of fruit were 191,298.88 and 0.20 kg CO2-eq, respectively. In addition, the current study revealed that the highest CO2-eq emissions per tonne of fruit were observed in energy use (fuel consumption) for field operations, corresponding to 40.49% of the total emissions per tonne of product.